The Efficiency and Resilience Dilemma : Economic Analysis of the Downstream Fossil Energy Industry Amidst the National Energy Transition - Feraliza Widanti; M. Sidik Boedoyo; Sri Murtiana (International Journal of Technology and Education Research, 2025)
Indonesia's dependence on fossil fuels remains strong despite national policy prioritizing the transition to net zero emissions by 2060 as a strategic goal. The downstream fossil fuel sector, particularly petroleum fuel processing and distribution, plays a crucial role in maintaining energy security and national economic stability. However, the dominance of state-owned enterprises, limited refinery capacity, and high subsidy policies create a dilemma between economic efficiency and energy security needs. This study aims to analyze the performance and economic structure of the downstream fossil energy industry in Indonesia using an industrial economics approach to understand the relationship between market structure, business behavior, and industry performance in the context of the national energy transition. The research method used is a qualitative - descriptive approach through literature studies, secondary data analysis from the Ministry of Energy and Mineral Resources, Statistics Indonesia, the Ministry of Finance, and reports from international institutions such as the International Energy Agency (IEA) and the UNFCCC. The analysis is based on the Structure Conduct Performance (SCP) framework to identify the influence of market structure on the efficiency and competitiveness of the downstream fossil fuel sector. The data analyzed includes market share, subsidy levels, contribution to GDP, and indicators of economic efficiency and national carbon emissions. The analysis shows that the market structure of Indonesia's downstream fossil fuel sector remains oligopolistic, with strong dominance by state-owned enterprises (SOEs) leading to low levels of competition and innovation. Large energy subsidies cause price distortions and significant fiscal burdens, while investments in new refinery projects have yet to show optimal results. These conditions have resulted in economic inefficiency and dependence on fuel imports, which in turn weakens national energy security. This study concludes that structural reforms, increased market efficiency, and the gradual integration of fossil fuels and new and renewable energy are important steps toward achieving a balance between economic efficiency and energy security during the transition to a low carbon economy.